A Dedication of a Naos to Skorpon’s Ourania in Ascalon (Ashkelon) — Illustrations - Ecker, Avner (Kernos, 2018)
An inscribed marble gable found near the ancient city center of Ascalon (modern Ashkelon) is published. The inscription (of AD 220) records the erection and dedication of a temple in honor of the goddess “Ourania of Skorpon”. Ourania Aphrodite was a resident deity in Ascalon and this appears to be the first tangible piece of evidence confirming the ancient ties linking her to the city. The word egersitheos, revivifier of a deity, in this inscription is otherwise unattested.